PENGARUH AUDITOR INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN PADA BANK PERKREDITAN RAKYAT DI JAWA TENGAH - Shabrina Rahutami Nur Amalia; Herry Laksito (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to examine the influence of Internal Auditor on financial reporting quality. Financial reporting is important part as considered thing for their decision maker. Thus, financial reporting quality needs to be overseen because of that influence on stakeholders decision. Nowadays, internal audit role is beamed as one of important role to improve financial reporting quality.This study uses primary data with questionnaires sent to internal audit directors of public credit bank in some city in Central Java. Sampling method that used is convenient sampling. Samples are choosen based on the easiness to control the questionnaires. This study uses 96 samples of Bank of Public Credit and there are 49 questionnaires which is returned. Because there are 3 outliers, the data that can be processed is 46. Statistic tool that used in this study is logistic regression. Before using logistic regression, questionnaires are tested by the validity and reliability testing.The result of this study indicate that internal auditor influences the financial reporting quality. Coordination and coorperation between internal auditor and eksternal auditor have positive influence on improvement of financial reporting quality. The greater involvement of internal auditor in overseeing financial reporting reliability will improve financial reporting quality.